Virtudes (Oporto): Exhibition at the Google Arts & Culture. From a Project Lab in Classroom to a "real" Cultural Management Program - Rosas, Lúcia (2017)
The Virtudes (Oporto): Exhibition at the Google Arts & Culture projects innovativecharacter resides in the possibility of implementing an integrated cultural managementprogram applied to a concrete object the Virtudes urban space of a scientificinvestigation that is oriented and put to practice as a heritage laboratory, both inside theclassroom and in fieldwork contexts. The Virtudes is the only historic and public gardenincluded in the UNESCO Historic Centre of Oporto site. With this project we intend to:1) create a virtual exhibition in a free access virtual platform (Google Arts & Culture); 2)create an integrated cultural management program solely focused on this urban space,which would also include the following activities: a physical exhibition, a catalogue,artistic workshops developed for different segments of the public and roundtables,exploring a bottom-up approach that seeks to profoundly involve and engage both thestudents and the local community in it.With this paper, we intend to not only present the pedagogical methodologyemployed to achieve the projected goals but also to ponder the results of theaforementioned methodologies, especially concerning the pivotal role they had in theenhancement of the students capabilities, their acquisition of competences, theirrespective involvement in the project and the obtained results.